Chemo-profiling of methanolic and ether oleoresins of Salvia coccinea and in vitro pesticidal evaluation with in silico molecular docking and ADME/Tox studies - Nagarkoti, Kirti; Prakash, Om; Rawat, Avneesh; Kabdal, Tanuja; Kumar, Ravendra; Srivastava, Ravi Mohan; Kumar, Satya; Rawat, Dharmendra Singh (European Journal of Chemistry, 2023)
The objective of the present study was to examine the chemical compositions of Salvia coccinea oleoresins prepared in methanol and petroleum ether. GC-MS analysis of Salvia coccinea methanolic oleoresin (SCMO) and Salvia coccinea ether oleoresin (SCEO) resulted in the identification of 15 and 12 constituents, comprising 84.7 and 81.2% of the total composition, respectively. Both SCMO and SCEO varied in their chemical composition in terms of quantity, namely, oleic acid (22.3-25.9%), palmitic acid (8.9-8.4%), stigmasta-3,5-dien-7-one (3.4-11.8%), stigmasterol acetate (3.5-5.3%), neophytadiene (4.8-1.7%), phytol (1.6-7.8%) and phthalic acid (2.1-3.1%). In addition to the qualitative differences between SCMO and SCEO concomitantly, both oleoresins were examined for their pesticidal activities. Oleoresins demonstrated significant nematicidal activity against Meloidogyne incognita, insecticidal activity against Lipaphis erysimi, antifungal activity against Curvularia lunata, and antibacterial activity against Staphylococcus aureus. For nematicidal activity, SCMO and SCEO exhibited a high mortality of 65.66±1.69 and 54.33±1.24 and egg hatching inhibition of 26.33±1.20and 33.33±1.24 at 200 μg/mL. Similarly, SCMO and SCEO exhibited excellent insecticidal activity with 94.87±1.44 % and 86.75±1.85 % mortality at 1000 μg/mL. However, both oleoresins exhibited moderate antifungal and antibacterial activities compared to standards. Due to the quantitative difference in chemical composition and the presence of several phytoconstituents that were absent in SCEO, SCMO displayed stronger pesticidal effects than SCEO. To estimate the binding energy and structure-activity relationships between chemical constituents and pesticidal activities, in silico molecular docking and ADME/Tox studies have also been performed using a web-based online tool. On the basis of the present study, it is inferred that the herb Salvia coccinea might be a good source of phytochemicals and can be used for the development of herbal-based pesticides/formulations after proper clinical trials.